The Relationship of Genetic Diversity of Human Immunodeficiency Virus-1 with Acquired Drug Resistance Mutation in HIV Patients on First-Lines Antiretroviral Therapy - Efrida Efrida; Andani Eka Putra; Ida Parwati; Jamsari Jamsari (Majalah Kedokteran Andalas, 2022)
Aim: This study aims to determine the relationship of HIV-1 genetic diversity with acquired drug resistance mutation in HIV-1 patients who receive first-line antiretroviral drugs at RSUP Dr. M. Djamil Padang. Methods: The study was conducted on 20 people with HIV who were diagnosed based on HIV-1 antibody screening tests using simple / rapid methods at the Central Laboratory of RSUP Dr. _ _ M. Djamil Padang and had received first-line ARV therapy for at least 6 months . Furthermore, proviral HIV-1 DNA extraction was carried out and amplification using a PCR (nested PCR technique) with a specific primer against reverse transcriptase at the Biomolecular Laboratory of the Microbiology Section of the Faculty of Medicine, Andalas University .  Result: The results showed that HIV-1 genetic diversity and changes in ARV regimens with the discovery of drug resistance mutations obtained for first-line ARVs were expected to be the basis for the management of HIV/AIDS patients. Conclusion: The conclusion of this study is that HIV-1 genetic diversity found is a form of recombinant CRF-AE and CRF- BC and subtypes A and B , a acquired drug resistance found is M184L and T215N (types of mutations that are resistant to NRTI- class ARVs)